Measurement of laryngeal elevation time using a flexible surface stretch sensor. (28th September 2020) - Hanaie, Kaoru; Yamamoto, Akio; Umehara, Ken; Bessho, Yusuke; Nakamoto, Hiroyuki; Nakayama, Kimiko; Sawada, Kaku; Osawa, Satoshi; Ogasawara, Takeshi; Tsuneishi, Syuichi; Wakasugi, Yoko; Ishikawa, Akira
Abstract: Background: Dysphagia is a growing health problem in aging societies. An observational cohort study targeting community‐dwelling populations revealed that 16% of elderly subjects present with dysphagia. There is a need in elderly communities for systematic dysphagia assessment. Objective: This study aimed to verify whether laryngeal elevation in the pharyngeal phase could be measured from the body surface using thin and flexible stretch sensors. Methods: Thirty‐two elderly subjects (17 males, 15 females; mean age ± SD: 89.2 ± 6.2 years) with suspected dysphagia underwent a swallowing contrast examination in which seven stretch sensors were attached to the front of the neck. The elongation of the sensors was measured and compared to the laryngeal elevation time values obtained using videofluorography. The sensor signal detected the laryngeal elevation start time, conclusion of the descent of the larynx, and the laryngeal elevation time. The respective laryngeal elevation times obtained using videofluorography and using the sensor were compared using the Bland–Altman method. Results: The laryngeal elevation time was 1.34 ± 0.46 s with the stretch sensor and 1.49 ± 0.56 s with videofluorography. There was a significant positive correlation between the duration obtained by both methods ( r  = .69, P  < .0001). A negative additional significant bias of −0.15 s (95% confidence interval −0.30 to −0.03, P  = .046) was noted in the laryngeal elevation time from the videofluorography measurement. Conclusion: Laryngeal elevation time can be measured non‐invasively from the neck surface using stretch sensors.